INTERRELATION BETWEEN THE DISPLAY OF SLOW CRUSTAL MOVEMENTS AND SEISMICITY IN CENTRAL ASIA - Ulomov V.I. (My University, 1981)
The relationship between recent crustal movements and evidence of seismicity on the active Turanian plate has been inferred by the author in 1966 from the results of integrated seismological and strain-metering investigations. On the basis of study of the faulting process which started actively to develop in 1965 and from a body of data for the seismic history of the region, official predictions of the large 1976 earthquakes (M = 7.0;M = 7.3) have been made.The area of flat desert struck by these earthquakes has been previously assigned a low level of seismic activity.Recent crustal movements in the Turanian plate have been shown to be conditioned by the singularities of the dynamics of the entire thickness of the Earth's crust and lithosphere.